The Two‐Column Aerosol Project: Phase I—Overview and impact of elevated aerosol layers on aerosol optical depth. Issue 1 (8th January 2016) - Berg, Larry K.; Fast, Jerome D.; Barnard, James C.; Burton, Sharon P.; Cairns, Brian; Chand, Duli; Comstock, Jennifer M.; Dunagan, Stephen; Ferrare, Richard A.; Flynn, Connor J.; Hair, Johnathan W.; Hostetler, Chris A.; et al.
Abstract: The Two‐Column Aerosol Project (TCAP), conducted from June 2012 through June 2013, was a unique study designed to provide a comprehensive data set that can be used to investigate a number of important climate science questions, including those related to aerosol mixing state and aerosol radiative forcing. The study was designed to sample the atmosphere between and within two atmospheric columns; one fixed near the coast of North America (over Cape Cod, MA) and a second moveable column over the Atlantic Ocean several hundred kilometers from the coast. The U.S. Department of Energy's (DOE) Atmospheric Radiation Measurement (ARM) Mobile Facility (AMF) was deployed at the base of the Cape Cod column, and the ARM Aerial Facility was utilized for the summer and winter intensive observation periods. One important finding from TCAP is that four of six nearly cloud‐free flight days had aerosol layers aloft in both the Cape Cod and maritime columns that were detected using the nadir pointing second‐generation NASA high‐spectral resolution lidar (HSRL‐2). These layers contributed up to 60% of the total observed aerosol optical depth (AOD). Many of these layers were also intercepted by the aircraft configured for in situ sampling, and the aerosol in the layers was found to have increased amounts of biomass burning material and nitrate compared to aerosol found near the surface. In addition, while there was a great deal of spatial and day‐to‐day variability in the aerosol chemical composition and optical properties, no systematic differences between the two columns were observed. Key Points: TCAP provides a data set to investigate science questions and evaluate model performance There is a large amount of variability in aerosol properties near northeast coast of North America Aerosol layers aloft have a large impact on aerosol optical depth